Safety of thoracic pedicle screw application using the funnel technique in Asians: a cadaveric evaluation - Chan, Chris Yin Wei (Springer Verlag, 2010)
The objective of this cadaveric study is to determine the safety and outcome of thoracic pedicle screw placement in Asians using the funnel technique. Pedicle screws have superior biomechanical as well as clinical data when compared to other methods of instrumentation. However, misplacement in the thoracic spine can result in major neurological implications. There is great variability of the thoracic pedicle morphometry between the Western and the Asian population. The feasibility of thoracic pedicle screw insertion in Asians has not been fully elucidated yet. A pre-insertion radiograph was performed and surgeons were blinded to the morphometry of the thoracic pedicles. 240 pedicle screws were inserted in ten Asian cadavers from T1 to T12 using the funnel technique. 5.0 mm screws were used from T1 to T6 while 6.0 mm screws were used from T7 to T12. Perforations were detected by direct visualization via a wide laminectomy. The narrowest pedicles are found between T3 and T6. T5 pedicle width is smallest measuring 4.1 ± 1.3 mm. There were 24 (10.0%) Grade 1 perforations and only 1 (0.4%) Grade 2 perforation. Grade 2 or worse perforation is considered significant perforation which would threaten the neural structures. There were twice as many lateral and inferior perforations compared to medial perforations. 48.0% of the perforations occurred at T1, T2 and T3 pedicles. Pedicle fracture occurred in 10.4% of pedicles. Intra-operatively, the absence of funnel was found in 24.5% of pedicles. In conclusion, thoracic pedicle screws using 5.0 mm at T1–T6 and 6.0 mm at T7–T12 can be inserted safely in Asian cadavers using the funnel technique despite having smaller thoracic pedicle morphometry.